A novel computational model for cerebral blood flow rate control mechanisms to evaluate physiological cases. (September 2022) - Bozkurt, Selim; Volkan Yilmaz, A.; Bakaya, Kaushiki; Bharadwaj, Aniket; Safak, Koray K.
Highlights: A new numerical model simulating interaction among cerebrovascular CO2 and O2 reactivities, static cerebral autoregulatory function and systemic arteriolar regulation was developed. The new numerical model was evaluated by simulating cerebral blood flow rate in heart failure, impaired cerebral autoregulation due to malignant hypertension, hyper and hypoventilation and hypoxemia. Simulation results were in a good agreement with the data reported in literature for the simulated physiological cases. The developed model can be used to evaluate clinical scenarios and treatment techniques for different diseases affecting cerebral blood flow rate. Abstract: In this study, a new numerical model simulating interaction among static cerebral autoregulation, cerebrovascular CO2 and O2 reactivities and systemic peripheral resistance regulation was developed and integrated into a cardiovascular system model including heart chambers, systemic and pulmonary circulations, and cerebral circulation with Circle of Willis. Simulations were performed to evaluate cerebral blood flow in a healthy condition, effect of altered static cerebral autoregulation in heart failure, effect of impaired static cerebral autoregulation in malignant hypertension, effects of arterial CO2 and O2 pressures in hypercapnia, hypocapnia and hypoxemia on cerebral blood flow. Also, sensitivity analysis was performed to assess influence of arterial CO2 and O2 pressure, aortic pressure set point in the cerebral flow autoregulatory function, systemic peripheral resistance, left ventricular active and passive properties on the cerebral blood flow rate. There was a high and positive correlation between cerebral blood flow rate and arterial CO2 pressure whereas left ventricular contractility influenced cerebral blood flow rate slightly. Cerebral blood flow rate in the healthy condition, heart failure, malignant hypertension, hypercapnia, hypocapnia and hypoxemia was 721 mL/min, 606 mL/min, 1313 mL/min, 950 mL/min, 504 mL/min and 972 mL/min, respectively. Simulation results and sensitivity analysis showed that the new numerical model can be used to evaluate cerebral blood flow in various physiological cases.